On A Rough Cayley Graph Related to Conjugacy Classes - Ali Asghar Talebi; S. Omidbakhsh Amiri (IndoMS, 2020)
In this paper, we discuss concepts of lower and upper approximations edge Cayley graphs of Cayley graphs with respect to conjugacy classes. Also, we expand rough approximation to pseudo-Cayley graphs and introduce concept of lower and upper approximations vertex pseudo-Cayley graphs of them with respect to a conjugacy classes. In the following, we discuss the properties of automorphisms in the Cayley rough graphs.